PERENCANAAN PEMBELAJARAN TEMATIK BERBASIS KEARIFAN LOKAL DI SD MUHAMMADIYAH I MALANG - Putri Utami, Ima Wahyu; Suwandayani, Beti Istanti (Prodi PGSD FKIP Universitas Sarjanawiyata Tamansiswa, 2018)
The development in the digital era also accompanies the development in the world of education. The implementation of the 2013 curriculum requires careful planning to produce quality output. This planning begins with preparing prota, promes, RPP. This study aims to analyze thematic learning planning based on local wisdom, to describe the supporting and inhibiting factors and to describe the effort done by the school to overcome the problem. This research uses qualitative descriptive research conducted at SD Muhammadiyah I Malang, data collection techniques used, among others, observation, interview and documentation. And the results of this research shows that teachers at SD Muhammadiyah I Malang have implemented a local wisdom-based learning plan before teaching and learning activities begin. Supporting factors of quality human resources, and adequate infrastructure facilities. While the inhibiting factor is the implementation of local wisdom learning for the activities of the visit takes a long time. To overcome these problems the school provides facilities for teachers to attend seminars, training and workshop.